Conservation units seen as drivers of sustainable development in Brazil and their correlations with the 2030 Agenda - Medeiros, Débora de Macêdo; Carvalho, Rodrigo Guimarães de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
Thinking about sustainable development is increasingly necessary for the continuity of all species in the biosphere. Over time, natural resources become scarcer, enabling conflicts and wars to be generated. Thus, this study aims to show the relevance of conservation units as territories that are necessary and supported by Law 9,985/2000 for the promotion of a sustainable culture in the country. But also, the aim was to prove the relationship of conservation units with the Sustainable Development Goals, proposed by the United Nations in 2015. For this study, the bibliographic and documentary research technique was used. At the end of the analysis, we can observe that the existence of conservation units and knowledge about them stimulates economic development linked to environmental care, facilitating the maintenance of social homeostasis and ecosystems. In addition to being directly linked to the SDGs and the concern for current and future generations.